Analysis of technical-tactical training tasks of u-16 female handball teams - Dallegrave, Eduardo José; Salles, William das Neves; Maciel, Larissa Fernanda Porto; Collet, Carine; Vieira do Nascimento, Juarez; Folle, Alexandra (Journal of Physical Education (Maningá), 2021)
The aim of the study was to analyze the technical-tactical training tasks of U-16 female handball teams. In this descriptive, quantitative and observational study, two coaches and 27 athletes from the cadet (U-16) category of two women's handball teams from the state of Santa Catarina (Brazil) were investigated. The data were collected through systematic and indirect observation (filming) of 36 training sessions, transcribed and analyzed from the Integral System for the Analysis of Training (SIATE). The data treatment was based on descriptive (frequency) and inferential statistics (hierarchical-multilevel modeling), using SPSS 23.0 software and program R. In the 336 tasks analyzed, it was observed that the sessions prioritized games and competition as means of training and tactical-technical conduct as the content type. The coaches used an undulatory model in the structuring of the tasks in the investigated microcycles, both teams prioritizing the use of training situations similar to the requirements of official handball matches.